2022
DOI: 10.3390/jcm11164865
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in Epidermal Differentiation Complex Genes as Predictive Biomarkers for Atopic Eczema, Allergic Sensitization, and Eczema-Associated Asthma in a 6-Year Follow-Up Case–Control Study in Children

Abstract: Atopic eczema is the most common chronic inflammatory skin disease of early childhood and is often the first manifestation of atopic march. Therefore, one challenge is to identify the risk factors associated with atopic eczema that may also be predictors of atopic disease progression. The aim of this study was to investigate the association of SNPs in hornerin (HRNR) and filaggrin-2 (FLG2) genes with childhood atopic eczema, as well as other atopic phenotypes. Genotyping for HRNR and FLG2 was performed in 188 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…In particular, candidate-gene studies have identified the genetic factors responsible for the impaired skin barrier, which is influenced by polymorphisms located within the Epidermal Differentiation Complex cluster (EDC). This cluster consists of more than fifty genes that encode proteins involved in the final differentiation and cornification of keratinocytes within the 1q21 chromosomal region [ 12 , 13 ]. Furthermore, the inflammatory aspect of AD has been associated with cytokines located within the Th2 cluster on the 5q31.1 locus [ 14 ].…”
Section: Genetics Of Atopic Dermatitismentioning
confidence: 99%
“…In particular, candidate-gene studies have identified the genetic factors responsible for the impaired skin barrier, which is influenced by polymorphisms located within the Epidermal Differentiation Complex cluster (EDC). This cluster consists of more than fifty genes that encode proteins involved in the final differentiation and cornification of keratinocytes within the 1q21 chromosomal region [ 12 , 13 ]. Furthermore, the inflammatory aspect of AD has been associated with cytokines located within the Th2 cluster on the 5q31.1 locus [ 14 ].…”
Section: Genetics Of Atopic Dermatitismentioning
confidence: 99%
“…In particular, 53 out of 99 studies (54%) examined participants of European ancestry (Table 1) and 46 (46%) of Asian ancestry (Table 2). Studies conducted in Euro-pean participants focused on the FLG (n = 27, 27%), TLR2 [41][42][43][44][45][46][47] (n = 7, 7%), IL10 [48][49][50][51][52][53][54] (n = 7, 7%), 11q13.5 [25,40,[55][56][57] (n = 5, 5%), IL13 [19,49,52,58] (n = 4, 4%), IL4 [49][50][51] (n = 3, 3%), HRNR [25,56,59] (n = 3, 3%) and IL6 [50,51,53] (n = 3, 3%) loci, while evidence for possible association for relevant genes were examined by a total of two studies [19,42,44,50,51,53,54,[60][61][62][63][64][65]…”
Section: Studies Included In Our Analysismentioning
confidence: 99%
“…Although the function remains unknown, it is hypothesized that HRNR is associated with corni cation [5,6]. A genetic variant (rs87776) in HRNR was identi ed in the GWAS of AD as an independent susceptibility locus for AD [7,8], and Debinska et al demonstrated that HRNR rs87776[C] could contribute to the pathogenesis of AD [9]. Pallerin et al reported that the expression of HRNR was signi cantly decreased in the skin lesions of AD patients [10].…”
Section: Introductionmentioning
confidence: 99%